Progress and challenges of plant-derived nucleic acids as therapeutics in macrophage-mediated RNA therapy - Liu, Yu-Da; Chen, Hao-Ran; Zhang, Yao; Yan, Ge; Yan, Hao-Jie; Zhu, Qi; Peng, Li-Hua (Frontiers in Immunology, 2023)
Plant-derived nucleic acids, especially small RNAs have been proved by increasing evidence in the pharmacological activities and disease treatment values in macrophage meditated anti-tumor performance, immune regulating functions and antiviral activities.But the uptake, application and delivery strategies of RNAs as biodrugs are different from the small molecules and recombinant protein drugs. This article summarizes the reported evidence for cross-kingdom regulation by plant derived functional mRNAs and miRNAs. Based on that, their involvement and potentials in macrophage-mediated anti-tumor/inflammatory therapies are mainly discussed, as well as the load prospect of plant RNAs in viruses and natural exosome vehicles, and their delivery to mammalian cells through macrophage were also summarized. This review is to provide evidence and views for the plant derived RNAs as next generation of drugs with application potential in nucleic acid-based bio-therapy.